2021
DOI: 10.1021/acsaem.1c01699
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Micropatterned, Narrow Line-Width Ni–Cu–Sn Front Contact Grid Pattern Using Maskless Direct-Write Lithography for Industrial Silicon Solar Cells

Abstract: An industry-ready strategic process for the fabrication of cost-effective, micropatterned Ni–Cu–Sn front contact metallization has been demonstrated using maskless direct-write lithography, which could effectively reduce the shadow loss and thereby enhance the efficiency of silicon solar cells by increasing the active area. This investigation also addresses the challenging issues in Ni–Cu–Sn metallization, such as adhesion of the seed layer, low-ohmic contact formation, background plating, and cell processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In this investigation, an eco‐friendly back contact aluminum paste was used for creating rear side metallization of the solar cell as demonstrated in our previous report. [ 26 ] Before the imprinting process, ANSYS 2D FEM‐based simulation tool was used to optimize the load/pressure for damage‐less imprinting process on poly (methyl methacrylate) (PMMA) coated solar cells. Based on the simulation studies, a cost‐effective process flow was used for fabricating the NIL Ni hard stamps using electroless deposition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this investigation, an eco‐friendly back contact aluminum paste was used for creating rear side metallization of the solar cell as demonstrated in our previous report. [ 26 ] Before the imprinting process, ANSYS 2D FEM‐based simulation tool was used to optimize the load/pressure for damage‐less imprinting process on poly (methyl methacrylate) (PMMA) coated solar cells. Based on the simulation studies, a cost‐effective process flow was used for fabricating the NIL Ni hard stamps using electroless deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The sheet resistance of the aluminum layer after annealing process was estimated to be 0.45 Ω □ À1 , which shows better conductivity compared to commercial silicon solar cells. [26] Scheme 1. Process flow adopted for fabrication of Ni-Cu-Sn front contact metallization using nanoimprint lithography technique.…”
Section: Aluminum Rear Contact Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…In homojunction c-Si cells with direct contact between the metal and Si, this barrier layer is usually nickel (Ni) and is usually annealed to form an interfacial nickel silicide layer (NiSi X ). The annealed Ni layer is also understood to improve adhesion and reduce contact resistance. A number of studies have tested for the downward diffusion of Cu (into cells) through the Ni barrier by means of accelerated testing at elevated temperatures (usually 200 °C), with detrimental degradation noted only when the Ni layer is insufficiently thick (<∼200 nm). , It is assumed that with sufficiently thick Ni barriers, the downward ingress of Cu is prevented both by the formation of NiSi X layer at the bottom of the stack and alloying at the Ni–Cu interface. ,, However, one study showed detrimental Cu precipitates underneath Ni diffusion barriers after 200 °C heat treatments and rapid cooling, suggesting that downward Cu may somehow defeat Ni barriers at moderate temperatures but that slow cooling inhibits the formation of performance-limiting extended Cu defects …”
Section: Introductionmentioning
confidence: 99%